2015
DOI: 10.1055/s-0034-1392150
|View full text |Cite
|
Sign up to set email alerts
|

Initial human experience of endoscopic ultrasound-guided photodynamic therapy with a novel photosensitizer and a flexible laser-light catheter

Abstract: These preliminary data suggest that EUS-guided PDT with a second-generation photosensitizer and a flexible laser probe is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 11 publications
0
52
0
Order By: Relevance
“…Currently, no data exist with respect to a positive effect of surgery on overall survival in small (<2 cm) non‐functioning pancreatic neuroendocrine tumors (PNET) . Given the considerable risks related to pancreatic surgery, a minimally invasive endoscopic ultrasonography (EUS)‐guided ablative technique might therefore have a role in this setting …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no data exist with respect to a positive effect of surgery on overall survival in small (<2 cm) non‐functioning pancreatic neuroendocrine tumors (PNET) . Given the considerable risks related to pancreatic surgery, a minimally invasive endoscopic ultrasonography (EUS)‐guided ablative technique might therefore have a role in this setting …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Given the considerable risks related to pancreatic surgery, a minimally invasive endoscopic ultrasonography (EUS)-guided ablative technique might therefore have a role in this setting. [3][4][5][6] A pilot study using ethanol ablation to treat PNET showed that the complete ablation rate was 61%; however, pancreatitis occurred in 27% of cases. 7 Different methods of improving ablative efficacy, as well as avoiding the risk of pancreatitis, should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical PDT photosensitisers such as chlorin e 6 or mTHPC are administered using a delivery system to improve water solubility consisting of an emulsion or liposomes (eg Verteporfin, which is formulated in liposomes as Visudyne) 9, 10 . The clinical formulation of chlorin e 6 (Photolon) contains polyvinylprrrolidone (PVP) which is a synthetic neutral polymer used to aid drug dissolution and disaggregation 33, 34 . There are several recent studies investigating new routes to improve chlorin e 6 delivery using other solubilising agents 3537 and nanoparticles 38, 39 which underscore the interest in improving the pharmacokinetic properties of this photosensitiser.…”
Section: Introductionmentioning
confidence: 99%
“…The first clinical experience with EUS-PDT in pancreatic cancer has been published in 2015 [53]. Four patients with locally advanced pancreaticobiliary cancers were included.…”
Section: Endoscopic Ultrasound-guided Tumor Ablationmentioning
confidence: 99%